Effect of age, gender, and body mass index on peak expiratory flow rate and other pulmonary function tests in healthy individuals in the age group 18-60 years - Mankar, Komal; M, Sunitha; Dindugala, Ramu (National journal of physiology, pharmacy and pharmacology, 2022)
Ageing; Body Mass Index; Chronic Obstructive Pulmonary Disease; Healthy Individuals; Peak Expiratory Flow Rate; Pulmonary Function Tests INTRODUCTION When God created human beings, he endowed them with energy, wisdom and intellect, brains for acquiring knowledge and various organs for doing work. Respiratory tract may be rightly regarded as the gateway for nutrition of the cells of the body. [...]an efficient respiratory mechanics with patent airways is important in regulating the overall health and well-being. [1] Pulmonary function is known to differ with subject's age, sex, race, ethnicity, socioeconomic status, cultural factors, and geographical region and is related to subject's height, weight and body mass index (BMI) after adjusting for other factors such as age, race, gender, asthma, and smoking status in population that are at risk for impaired lung function. [1112] Ovarian hormones like Progesterone and estrogen does affect the respiratory system. [...]the major step forward in determining the functional status of the lungs is pulmonary function testing as it correlates the volume of air moving in and out of the lungs, lung and chest wall stiffness, diffusion properties of the membrane through which the gas moves and response of the lungs to chest physical therapy procedures.